Soil microbial communities in contrasting environments show a common core of species linked to Maytenus senegalensis shrubs - Díaz-Santiago, Elena; Sadio, Thiaba D.; Diéme, Joseph S.; Hurtado-Martínez, Miguel; Kindler, Christian; Manrique, Esteban; Pugnaire, Francisco I. (Frontiers in Microbiology, 2026)
IntroductionThe existence of a core microbiota specific to a plant species, or the set of microorganisms shared by all plant individuals of the species, is of utmost importance because of its many conceptual and practical consequences. The core microbiota is assumed to gather the most ecologically and functionally relevant microorganisms associated to a plant in a given environment, presumably establishing positive feedbacks that support its persistence and performance in a plant community.MethodsWe tested the existence of a potential core microbiota in Maytenus senegalensis shrubs in two contrasted, distant ecosystems; a dry environment (Almeria, Spain) and a relatively wetter ecosystem (Dakar, Senegal).ResultsSoil microbial community structure widely differed between sites influenced by soil and climate. However, a subset of microbial phylotypes appeared consistently associated to all M. senegalensis plants across our two disparate ecosystems while they were absent in the surrounding soil, suggesting the presence of a core microbiota in M. senegalensis.DiscussionMicrobiota had an effect on germination that differed between sites, perhaps due to climatic constrains. We show that the assembly of understory microbial communities depends on the plant’s sorting effect on the surrounding soil microbiota, plus some other taxa likely transferred by seeds; this assembly mechanism is relevant for the coevolution of plants and microorganisms, and critical for potential community responses to environmental changes.